Paracrine Effects of Recombinant Human Adiponectin Promote Bone Regeneration - Gong, Yanping; Wang, Yang; Zhang, Yiqing; Wang, Liangchen; Wan, Lijuan; Zu, Yuan; Li, Chunlin; Wang, Xin; Cui, Zhong-Kai (Frontiers in Cell and Developmental Biology, 2021)
Bone regeneration is a delicate physiological process. Nonunion and delayed fracture healing remains a great challenge in nowadays clinical practice. Bone and fat hold a close relationship to remain balanced through hormones and cytokines. Adiponectin is a well-known protein to maintain the hemostasis, which may be an interesting target for fracture healing. Herein, we provided a facile and efficient method to obtain high purity and high yield recombinant human adiponectin (ADPN). The biocompatibility and the pharmaceutical behaviors were evaluated in the Sprague Dawley rats. The paracrine effects of adiponectin on bone fracture healing were investigated with a rat tibia fracture model via intra-bone injection. Significantly accelerated bone healing was observed in the medulla injection group, indicating the paracrine effects of adiponectin could be potentially utilized for clinical treatments. The underlying mechanism was primarily assessed and the expression of osteogenic markers, including the bone morphogenic protein 2, alkaline phosphatase and osteocalcin, along with the adiponectin receptor 1 (AdipoR1) was markedly increased at the fracture site. The increased bone healing of ADPN treatment may result from both enhanced osteogenic proliferation as well as differentiation. Cell experiments confirmed that the expression of osteogenesis markers increased significantly in ADPN treatment groups; while decreased when the expression of AdipoR1 was knocked down by siRNA. Our study provided a feasible and efficacious way for bone fracture treatment with local administration of ADPN, which could be rapidly translated into the clinics.